ANALISIS HUBUNGAN PERSEPSI MAHASISWA TERHADAP PENINGKATAN BIAYA PENDIDIKAN DAN KUALITAS LAYANAN PENDIDIKAN PADA MAHASISWA ANGKATAN 2024-2025 DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TRIBUANA KALABAHI - Oktovianus Sandy; Alboin Selly; Agnes M. Kolly (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the relationship between the increase in educational fees and the quality of educational services among the 2024–2025 cohort of students at the Faculty of Teacher Training and Education (FKIP), Universitas Tribuana Kalabahi. The background of this research is based on adjustments in educational fees (tuition and credit fees) that demand improvements in professional, responsive, and timely academic service quality. The research method used is quantitative with a correlational approach. The research population consisted of 525 students, with a sample size of 84 respondents determined through the Slovin formula. Data collection utilized a five-point Likert scale questionnaire, ranging from strongly agree, agree, neutral/undecided, disagree, to strongly disagree. The data analysis techniques applied included descriptive statistical analysis, validity and reliability tests, Pearson Product-Moment correlation test, significance test (t-test), and the coefficient of determination. The results of the correlation analysis showed a coefficient value of 0.329 with a significance of 0.002 ($p < 0.05$), which means there is a positive and significant relationship between the increase in educational fees and service quality. The coefficient of determination analysis showed that the educational fees variable contributed 10.9% to service quality, while the remaining 89.1% was influenced by other factors. This study concludes that the increase in educational fees aligns with the improvement of service quality, falling within the low but definite correlation category. The university is advised to increase transparency in financial management and to continuously optimize faculty performance and academic calendar punctuality to meet student expectations.